Diatom Responses to Holocene Environmental Changes in the Tiền Delta - Mekong River System - Nguyễn, Thị Thu Cúc (VNU, 2014)
The environmental changes in the Tiền delta during the Holocene were revealed by diatom investigation of 3 deep boreholes along the coastal zone of the Mekong delta, Vietnam. The data shows that the studied area was transformed from a terrestrial condition to coastal area at about 8000 years BP. The dominance of marine diatoms species from 40m to 15m in the borehole LKBT2, from 36.5m to 18m in the borehole LKTB3and from 20m to 14 m in the borehole LKTB1 indicates that studied area at about 5000-7000 years BP was dominated by marine environment such as lagoon or estuary. This change is a result of the Flandrian transgression. The sandy bar or supratidal flat characterized by the strong decrease of diatoms in number of species and individuals shows a regression time at about 4000 years BP. The dominance of diatoms in the uppermost part in the 3 boreholes shows a coastal environment in the late Holocene.